Kepuasan wisatawan terhadap kualitas pelayanan usaha cooking class di kecamatan ubud kabupaten gianyar - Ni Putu Ida Trisnadewi; IB Ketut Astina; I Nyoman Tri Sutaguna (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2022)
This study aims to determine the quality of cooking class business services and tourist satisfaction with the quality of cooking class business services in Ubud District, Gianyar Regency. This research is based on a decrease in tourist visits in the cooking class business where the conditions are inversely proportional to an increase in tourists to Ubud.Data collection techniques through observation, structured interviews, literature study, documentation and questionnaires. In this study, to determine the sample, a cluster random sampling technique is used to get a sampling from people in country and regency. The informants in this study were cooking class teachers. The type of data used is qualitative and quantitative data. As for the data sources, namely primary data and secondary data. Data analysis techniques using Likert scale analysis and importance performance analysis (IPA).Based on the results of this study, the quality of cooking class business services in Ubud from 100 tourists to 16 indicators that affect the level of tourist satisfaction obtained an average total performance rating of 4.15, which means tourists assess the quality of cooking class business services in Ubud Good based on indicators from each - each variable. Meanwhile, tourist satisfaction with cooking class business services obtained from the level of suitability divided by 16 indicators that affect the level of satisfaction obtained an average suitability level score of 89.14% which means tourists feel satisfied. Keywords: Tourist satisfaction, Service Quality, Cooking class